Risk Factors For Coronary Heart Disease : A Case Control Study - Zodpey Sanjay P; Kulkarni Hemant R; Vasudeo N. D; Kulkarni S. W (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the role of different risk factors in causation of CHD. Objective: To identify the risk factors contributing to the outcome of CHD. Design: Pair matched case-control study. Setting: Government Medical college, Nagpur, India, a tertiary care hospital. Participants: The study included 294 incident cases of CHD diagnosed by standard criteria. Each case was pair matched with one control for age and sex. Controls were selected from subjects attending the hospital for conditions other than CHD. Main Outcome Measure: CHD. Study variable: Socio-economic status (SES), physical inactivity (PI), family history of CHD, type A personality (TAP), cigarette smoking (CS), alcohol consumption (AC), obesity, oral contraceptive use (OC use), diabetes mellitus (DM), hypertension (HT) and total serum cholesterol TSC). Results: On univariate analysis all the 11 risk factors were significantly associated with CHD. Conditional multiple logistic regression identified significant association of SES (OR 2.92, 95% CI 2.28-3.73), PI (OR 2.03, 95% CI 1.56-2.62), OC use (OR 3.96, 95% CI 1.11-14.02), obesity (OR 1.62, 95% CI 1.15-2.27), DM (OR 2.17, 95% CI 1.13-4.13), HT (OR 4.23, 95% CI 2.56-6399), TSC (OR 3.84, 95% CI 2.58-5.72) and CHD. Estimates of attributable risk proportion and population attributable risk proportion for the significant factors confirmed their etiological role and impact of these factors on the development of CHD in this population. Conclusion: This study identified significance of SES, PI, OC use, obesity, DM, HT and TSC in multivariate environment in the outcome of CHD.